Demand and supply analysis of labor in the agriculture, mining and industrial sector in Jambi Province, Indonesia - Zulfanetti Zulfanetti; Fuad Muchlis; Rendra Rendra; Eristian Wibisono (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
The aim of this study is to analyze: 1) The development of labor demand and supply as well as the factors affecting the agriculture, mining and industry sectors in Jambi Province; (2) The factors that affect labor supply in Jambi Province; (3) The factors affecting labor demand in the agriculture, mining and industry sectors in Jambi Province. This study is used secondary data with multiple linear regression analysis tools. The results showed that the labor force growth rate was 3.13 per cent, the agricultural sector labor demand rate was 2.87 per cent, the mining sector labor demand rate was 16.07 per cent, the industrial sector labor demand rate was 7.78 per cent, the agricultural sector's GRDP growth rate was 14, 96 per cent, mining sector GRDP growth rate 28.04 per cent, agriculture sector GRDP growth rate 5.03 per cent, population growth rate 2.31 per cent, PMW growth rate 16.44 per cent, HDI growth rate 0.20 per cent, growth rate agricultural land area 1.66 per cent, investment growth rate in the agricultural sector 14.14 per cent, investment growth rate in the mining sector 91.94 per cent, investment growth rate in the industrial sector 321.78 per cent and growth rate in the number of industries 2.06%. The factors that influence the supply of labor are the variable population and the Provincial Minimum Wage. The factors that influence the demand for labor in the agricultural sector are GRDP variables in the agricultural sector. Factors affecting the demand for labor in the mining sector are the Provincial Minimum Wage and investment in the mining sector. Factors that influence the demand for labor in the industrial sector are the Provincial Minimum Wage.